Nipper the noisy puppy - Dale, Jenny; Rodgers, Frank, 1944- (New York : Aladdin Paperbacks, 2000)
Adam must confront his fear of dogs when he discovers that his new neighbors have a noisy puppy.
Keywords: Fear -- Juvenile fiction; Dogs -- Juvenile fiction